2012
DOI: 10.1371/journal.pone.0043343
|View full text |Cite
|
Sign up to set email alerts
|

RNA Inhibition Highlights Cyclin D1 as a Potential Therapeutic Target for Mantle Cell Lymphoma

Abstract: Mantle cell lymphoma is characterized by a genetic translocation results in aberrant overexpression of the CCND1 gene, which encodes cyclin D1. This protein functions as a regulator of the cell cycle progression, hence is considered to play an important role in the pathogenesis of the disease. In this study, we used RNA interference strategies to examine whether cyclin D1 might serve as a therapeutic target for mantle cell lymphoma. Knocking down cyclin D1 resulted in significant growth retardation, cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 17 publications
3
25
2
Order By: Relevance
“…In contrast, Weinstein et al . detected apoptosis in the GRANTA-519 and JEKO-1 lines eight days after CCND1 siRNA transfection [31]. In agreement with the study of Weinstein et al .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, Weinstein et al . detected apoptosis in the GRANTA-519 and JEKO-1 lines eight days after CCND1 siRNA transfection [31]. In agreement with the study of Weinstein et al .…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with the study of Weinstein et al . [31], our data indicate that CCND1 is essential in JEKO-1 (and UPN-1) cells. Apoptosis in JEKO-1 cells after CCND1 depletion was detected both in the Weinstein et al .…”
Section: Discussionmentioning
confidence: 66%
“…This raise the future possibility of purifying MCL derived exosomes from patient’s serum and harnessing them for the delivery of therapeutic payloads while exploiting their natural specifically towards MCL cells. Since exosomes could be taken up by monocytes as well, exosomes might be loaded with specific anti MCL molecules, such as siRNA molecules for cyclin D1, which was previously shown by us to decrease viability of MCL cells and induced cell apoptosis[48]. …”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo studies, we did not succeed in demonstrating gene silencing in a direct manner. However, former studies performed in vitro demonstrated that the silencing of cycD1 induces cell cycle arrest and cell death (9). These findings imply there should be a "selective force" against the targeted cells in which cycD1 was knocked down, interfering with the ability to detect the silencing of cycD1 in the BM of tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 97%
“…We previously showed that cycD1 down-regulation in MCL cell lines using RNAi inhibits proliferation and causes cell cycle arrest and apoptosis (9). However, the clinical application of this approach is hindered by the lack of appropriate systems that could deliver RNAi payloads to MCL cells in an efficient and safe manner (10,11).…”
mentioning
confidence: 99%